2022
DOI: 10.3748/wjg.v28.i35.5154
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol promotes epithelial mesenchymal transformation-mediated premetastatic niche formation of colorectal cancer by activating interaction between laminin-γ2 and integrin-β1

Abstract: BACKGROUND Colorectal cancer (CRC) is a common malignant tumor. Alcohol consumption is positively correlated with CRC malignant metastasis; however, the mechanism is unclear. The interaction between laminin-γ2 (LAMC2) and integrin-β1 (ITGB1) plays a role in premetastatic niche signaling, which may induce epithelial mesenchymal transformation (EMT) and lead to metastasis. AIM To investigate the effects of alcohol on CRC metastasis from the molecular mechanism of the prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Laminin 332 and 411 promote Epithelial to Mesenchymal Transition Marker in 2D and 3D Colon Cancer (42). Alcohol promotes EMT-mediated premetastatic niche formation of colorectal cancer via interaction between laminin-γ2 (43). All in all, LAMB overexpression and macrophages, monocytes, CD4_ The enrichment of T and CD cells was positively correlated, and in most tumor types, the expression of LAMBs was signi cantly positively correlated with the in ltration level of TAM, especially M2 like TAM, which could inhibit tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Laminin 332 and 411 promote Epithelial to Mesenchymal Transition Marker in 2D and 3D Colon Cancer (42). Alcohol promotes EMT-mediated premetastatic niche formation of colorectal cancer via interaction between laminin-γ2 (43). All in all, LAMB overexpression and macrophages, monocytes, CD4_ The enrichment of T and CD cells was positively correlated, and in most tumor types, the expression of LAMBs was signi cantly positively correlated with the in ltration level of TAM, especially M2 like TAM, which could inhibit tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, PFK inhibition increased glycolysis and upregulated HIF1α, promoting the reprogramming of stem cell transcription factors and aided tumor growth in patients [92]. In addition, alcohol encourages the interaction between LAMC2 and ITGB1, increasing p-FAK/FAK, snail, fibronectin, N-cadherin, and SATB1 while decreasing E-cadherin in the alcohol group compared to the non-alcohol group [93]. It suggests that alcohol may encourage CRC metastasis by molecular processes that change the pre-metastatic environment [93].…”
Section: Itgb1 Involvement In Ecm Remodelingmentioning
confidence: 99%
“…In addition, alcohol encourages the interaction between LAMC2 and ITGB1, increasing p-FAK/FAK, snail, fibronectin, N-cadherin, and SATB1 while decreasing E-cadherin in the alcohol group compared to the non-alcohol group [93]. It suggests that alcohol may encourage CRC metastasis by molecular processes that change the pre-metastatic environment [93]. In PDAC, activation of pancreatic stellate cells (PSCs) is a feature.…”
Section: Itgb1 Involvement In Ecm Remodelingmentioning
confidence: 99%
“…Data from in vitro cell culture studies and experimental models revealed that ethanol elevates epithelial mesenchymal transformation in CRC by activating laminin subunit gamma-2 and integrin beta 1 signals. 105 Ethanol and/or acetaldehyde mediates activation of transforming growth factor-beta/Runt-related transcription factor 3/ Snail axis and glycogen synthase kinase-3 beta/β-catenin/ monocyte chemoattractant protein 1 pathway, subsequently promotes aggressiveness of CRC. 106 107 Chronic alcohol intake promotes metastasis of CRC via the chemokine (C-C motif) ligand 5/AMP-activated protein kinase pathway-induced autophagy.…”
Section: Alcohol-associated Colon Cancermentioning
confidence: 99%